2002
DOI: 10.1067/mic.2002.124532
|View full text |Cite
|
Sign up to set email alerts
|

Hygienic hand antiseptics: Should they not have activity and label claims against viruses?

Abstract: Enteric and respiratory viruses are among the most frequent causes of human infections, and hands play an important role in the spread of these and many other viral diseases. Regular and proper hand hygiene by caregivers and food handlers in particular is essential to decontaminate hands and potentially interrupt such spread. What would be considered a proper decontamination of hands? Handwashing with regular soap and water is often considered sufficient, but what of hygienic handwash and handrub antiseptic pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
42
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 113 publications
0
42
0
1
Order By: Relevance
“…212 It has been shown that RSV can be carried and spread to others on the hands of caregivers. 213 Studies have shown that health care workers have acquired infection by performing activities such as feeding, diaper change, and playing with the RSV-infected infant. Caregivers who had contact only with surfaces contaminated with the infants' secretions or touched inanimate objects in patients' rooms also acquired RSV.…”
Section: Action Statement Profile Kas 11bmentioning
confidence: 99%
“…212 It has been shown that RSV can be carried and spread to others on the hands of caregivers. 213 Studies have shown that health care workers have acquired infection by performing activities such as feeding, diaper change, and playing with the RSV-infected infant. Caregivers who had contact only with surfaces contaminated with the infants' secretions or touched inanimate objects in patients' rooms also acquired RSV.…”
Section: Action Statement Profile Kas 11bmentioning
confidence: 99%
“…149 It has been shown that RSV as well as many other viruses can be carried and spread to others on the hands of caregivers. 150 Frequent hand-washing by health care workers has been shown to reduce RSV's nosocomial spread. 150 The Centers for Disease Control and Prevention published an extensive review of the hand-hygiene literature and made recommendations as to indications for hand-washing and hand antisepsis.…”
Section: Recommendation 9c Clinicians Should Educate Personnel and Famentioning
confidence: 99%
“…150 Frequent hand-washing by health care workers has been shown to reduce RSV's nosocomial spread. 150 The Centers for Disease Control and Prevention published an extensive review of the hand-hygiene literature and made recommendations as to indications for hand-washing and hand antisepsis. 151 Among the recommendations are that hands should be decontaminated before and after direct contact with patients, after contact with inanimate objects in the direct vicinity of the patient, and after removing gloves.…”
mentioning
confidence: 99%
“…While these are among the most frequent causes of community and hospital infection, viruses are also extremely important and are far more difficult to investigate. 99 Studies on hand hygiene have been mainly observational and may be subject to reactive biases because of the presence of an observer. 94 Blinding, randomisation and controlling for confounding variables may not be feasible.…”
Section: Scientific Evidence and The Organisational Complexity Of Hanmentioning
confidence: 99%